AB0881 Chondroitin Sulphate: Targeting Mitochondria for Osteoarthritis Therapy. (9th June 2015) - Calamia, V.; Lόpez-Armada, M.; Montell, E.; Vergés, J.; Ruiz-Romero, C.; Blanco, F.J.
Abstract : Background: In a recent proteomic study, we have demonstrated that mitochondrial dysregulation occurs in cartilage cells during osteoarthritis (OA). These findings suggest that mitochondria represent an attractive target for anti-OA pharmacotherapy. Objectives: In this study we have investigated the mitochondrial activity of OA human articular chondrocytes treated with chondroitin sulphate (CS). Methods: Chondrocytes were released by enzymatic digestion from OA human cartilages (n=8). The study was approved by the local ethic committee (Galician). Once reached 80% confluence, cells were treated with CS (Bioiberica, Spain) in presence or absence of different stimuli (IL1β, TNFα and LPS). Cells were analyzed by flow cytometry to measure the mitochondrial membrane potential (Δψm) using the probe JC-1 (10 mg/ml) and to evaluate the intracellular production of ROS using the dye DCFH-DA (10 μM). ATP Bioluminiscence Assay Kit (PerkinElmer) was utilized to measure the production of intracellular ATP. A commercial colorimetric assay kit (Sigma) was used to specifically quantify mitochondrial superoxide dismutase activity (SOD2). NO release was measured as nitrite concentration in 48 h culture supernatants by using the Griess assay. SPSS statistical software was used to determine statistical significance by using U-Mann Whitney test ( p ≤0.05). Results: At basal condition, a 64% increase in chondrocytes Δψm was observed after 48 hours treatment with CS 200 μg/mL. When chondrocytes were stimulated with TNFα, a significant depolarization was induced (Δψm decreased up to 41% and 39% respectively). Interestingly, also in this case, CS was able to increase chondrocytes Δψm up to 66%, partially counteracting the effect of TNFα. To determine mitochondrial function, we also assessed ATP production. Chondrocytes treatment with CS 200 μg/mL at 24 hours significantly increased ATP production compared to basal condition (0, 55 μM vs 0, 65 μM). After TNFα stimulation, ATP production fell to 0, 40 μM; but also in this case, CS was able to inhibit TNFα effect increasing the ATP synthesis up to 0, 62 μM. Furthermore, we have evaluated the effect of CS on NO and ROS production. Basal synthesis of NO was not modified by CS treatment. However, CS was able to reduce NO synthesis induced by IL1β (5ng/ml), TNFα (10ng/ml) or LPS (100μgr/ml). The NO levels were reduced after cytokine stimulation up to 21%, 32% and 31% respectively. On the other hand, in presence of IL1β, ROS production and SOD2 activity were increased. In this case, intracellular ROS production as well as SOD activity decreased in CS treated chondrocytes at an average of 80%. The decrease was more marked (up to 62%) when we specifically analysed the mitochondrial isoform of this important antioxidant enzyme (SOD2). Conclusions: In summary, CS improves mitochondrial activity in human OA chondrocytes by affecting several mitochondrial processes. The mitochondrial membrane hyperpolarization and the increased ATP production could correlate with a greater resistance of CS treated chondrocytes to apoptosis. Moreover, the reduction of NO and ROS levels, as well as the reduction of SOD2 activity, provide evidence of the effect of CS on oxidative stress regulation. Finally, we can conclude that mitochondria represent a new CS target for OA treatment. Disclosure of Interest: V. Calamia: None declared, M. Lόpez-Armada: None declared, E. Montell Employee of: Bioibérica, J. Vergés Employee of: Bioibérica, C. Ruiz-Romero: None declared, F. J. Blanco: None declared